Implementasi Kebijakan Pajak Progresif Bagi Kendaraan Bermotor - Lidya Octafiani Br Sinulingga; Muhammad Husni Thamrin Nasution; Beby Masitho Batubara (PERSPEKTIF, 2018)
Public policy has two main functions: budget and regulation. Similarly, the Progressive Tax Policy of Motor Vehicles regulated in the Regional Regulation of North Sumatra Province No. 1 of 2011 which began in force in 2012. This researcher uses descriptive qualitative research method. The data collection procedure used by interview, observation, documentation. Data analysis is done by data reduction, data presentation and conclusion. The results of this study indicate that the implementation of policies on the implementation of motor vehicle progressive taxes, including communication, human resources, executor attitude, and bureaucracy has been well implemented by Upt Samsat South Medan, namely: (1) Communication carried out externally by publishing a progressive tax to the public or taxpayer using print media and electronic media. (2) Human resources shall be carried out by preparing the personnel of the progressive tax service personnel of the vehicles in accordance with their respective fields of work and supported by adequate facilities and infrastructure of public services. (3) The executing attitude is carried out by Samsat employee by giving good service attitude to the taxpayers who pay the progressive tax in accordance with the operational standard of the established procedure; (4) Bureaucracy implemented implemented by simplifying the bureaucracy of vehicle tax payment service by forming working group, so taxpayers become easier in obtaining progressive tax service in Upt Samsat South Medan.